Regeneration rate after fission in the fissiparous sea star Allostichaster capensis (Asteroidea). - Rubilar, Tamara (2015)
Many studies have focused on the regeneration rate of arms in Asteroidea but no studies have focused on the regeneration rate after fission. Allostichaster capensis is a fissiparous sea star with a wide range of distribution. In Golfo Nuevo (42°46’49’’ S - 64°59’ 26’’ W) sea stars undergo fission every spring and summer and regenerate the rest of the year. To analyze the regeneration rate, we conducted an experiment with sea stars collected just before fission. After sea stars underwent fission, the length of the three non-regenerating and the three regenerating arms were measured weekly. The arm length (regenerating and non-regenerating) was used in non-Linear Mixed Effect models in order to account for within-individual correlation in different models. The regenerating arms regenerate according to a Quadratic model, while the non-regenerating arms regenerate according to a linear model. In the regenerating arms, the regeneration rate was estimated to be 0.1 mm.week-1 and in the non-regenerating arms, the growth rate was 0.004 mm.week -1. Sea stars regenerate ca. 20 % of the arm in one month, and it takes about 5 months to be completely regenerated. At the beginning, the regeneration rate is fast generating the growth of the arms, once the pyloric caeca and gonads are present inside the arms the regeneration rate slows down probably due to allocation to gametes and pyloric caeca and arms. The factors that regulate the regeneration rate are unknown. However, food availability and energy storage seem to play an important role.